Max Steiner: Composing, Casablanca, and the Golden Age of Film Music - Wegele, Peter (Rowman & Littlefield Publishers, 2014)
Max Steiner is one of the greatest—not to mention most prolific—composers of the Golden Age of Hollywood. The winner of three Academy Awards, Steiner’s credits include King Kong, The Informer, Gone with the Wind, Now, Voyager, Since You Went Away, Johnny Belinda, and The Caine Mutiny. Though known for timeless melodies that symbolize the glamor of Hollywood’s Golden Age, Steiner has also been hailed as a film scoring pioneer. In Max Steiner: Composing, Casablanca, and the Golden Age of Film Music, Peter Wegele unveils the man behind dozens of memorable scores, offering a portrait of the composer from a personal and professional point of view. Beginning with background on the history and techniques of film music, Wegele then examines Steiner’s musical innovations, some of which are still used today. This is followed by a thorough analysis of one of Steiner’s legendary scores—the music to Casablanca. More than eighty transcribed musical examples demonstrate how efficient, musically clever, and tremendously skilled the composer was when he wrote this score. Drawing on quotes, notes from production files, and excerpts from the original script for Casablanca, Wegele provides insight not only into the production history of the film, but also into the workings of Hollywood during the Golden Age. Including an appendix that compares Steiner with four other composers of his age—Erich Wolfgang Korngold, Alfred Newman, Franz Waxman, and Hugo Friedhofer—and a complete filmography of Steiner’s work, this book is an invaluable examination of the composer’s life and career. Film music composers, music scholars and students, directors, and anyone interested in film and music history will enjoy this detailed portrait of a musical genius.